Dietary Total Antioxidant Capacity, a Diet Quality Index Predicting Mortality Risk in US Adults: Evidence from the NIH-AARP Diet and Health Study - Kyungho Ha; Linda M. Liao; Rashmi Sinha; Ock K. Chun (MDPI AG, 2023)
Dietary total antioxidant capacity (TAC) is an index representing the total antioxidant power of antioxidants consumed via the diet. This study aimed to investigate the association between dietary TAC and mortality risk in the US adults using data from the NIH-AARP Diet and Health Study. A total of 468,733 adults aged 50-71 years were included. Dietary intake was assessed using a food frequency questionnaire. Dietary TAC from diet was calculated from antioxidants including vitamin C, vitamin E, carotenoids, and flavonoids, and TAC from dietary supplements was calculated from supplemental vitamin C, vitamin E, and beta-carotene. During a median follow-up of 23.1 years, 241,472 deaths were recorded. Dietary TAC was inversely associated with all-cause (hazard ratio (HR) for quintile 5 vs. quintile 1: 0.97, 95% confidence interval (CI): 0.96-0.99, p for trend < 0.0001) and cancer mortality (HR for quintile 5 vs. quintile 1: 0.93, 95% CI: 0.90-0.95, p for trend < 0.0001). However, dietary supplement TAC was inversely associated with cancer mortality risk only. These findings indicate that consuming a habitual diet high in antioxidants may reduce the risk of all-cause and cancer mortality and TAC from foods might confer greater health benefits than TAC from dietary supplements.